Development of the Political Culture of Management Staff is the Need of the Time - Halimmetova Rohatoy Davlatboevna (Global Scientific Publishing, 2022)
The article talks about the urgent tasks of training managerial personnel, that the development of their knowledge, skills and abilities is an important factor in ensuring the development of society
Keywords: management, innovation, new generation, manager, leader, leader, efficiency.